Bahasa Positif Guru Dalam Bimbingan dan Konseling Membentuk Karakter Positif Anak Usia Dini - Widyastuti, Ana (STKIP Muhammadiyah Pringsewu, 2018)
The child is a master imitator. He will imitate whatever he sees and hears. The attitude of a childs language is strongly influenced by the people around him, if a child is accustomed to listen to language and good attitude, then the children will also follow the language and be nice too, otherwise if the language and attitude of the adult bad or not good, then the child will also follow it. The teachers job is to provide counseling and guidance services, aiming to help the child know his or her shortcomings and strengths, helping the child to think positively in all situations, and helping the child feel comfortable in the school and environment. Language as a communication tool. Has an important role for everyone, especially in interacting? Language has an important role in the counseling process. Language mistakes in counseling should be avoided as much as possible. Selection of appropriate language as a successful effort of guidance and counseling service since early. Keywords: Positive Language, Teacher, Guidance and Counseling, Positive Character, Early Childhood